-3-5s=-7-6s

Simple and best practice solution for -3-5s=-7-6s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-5s=-7-6s equation:


Simplifying
-3 + -5s = -7 + -6s

Solving
-3 + -5s = -7 + -6s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '6s' to each side of the equation.
-3 + -5s + 6s = -7 + -6s + 6s

Combine like terms: -5s + 6s = 1s
-3 + 1s = -7 + -6s + 6s

Combine like terms: -6s + 6s = 0
-3 + 1s = -7 + 0
-3 + 1s = -7

Add '3' to each side of the equation.
-3 + 3 + 1s = -7 + 3

Combine like terms: -3 + 3 = 0
0 + 1s = -7 + 3
1s = -7 + 3

Combine like terms: -7 + 3 = -4
1s = -4

Divide each side by '1'.
s = -4

Simplifying
s = -4

See similar equations:

| x+x(.15)=315000 | | -6y+2=4-6y | | f(x)=5x^2-6x+5 | | A=pir^2+2pirh | | X^4-40X^2-33=0 | | 4(3n+1)=6(2n-1) | | 9j=-7+10j | | 24.3=12.4+2a | | -3x-2+1=-7 | | -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 | | 10p^2-90p=0 | | x-75x=6x | | 0.5x+0.3=1.2 |

Equations solver categories